Land distribution and income inequality in rice-growing villages in the Philippines, 1993, 1997 - Estudillo, Jonna P.; Hossain, Mahabub (The Philippine Review of Economics, 2003)
This paper examines the relationship between land distribution and income inequality in three rice-growing villages in the Philippines. One of our findings is that access to land has ceased to be the most important determinant of household income position, as farming and landless households have increasingly derived their incomes from non-farm economic activities. The association between land distribution and income distribution has weakened. Non-farm income has become an equalizing factor, which means that the development of the non-farm sector and the improved access of households to such markets have played a more decisive influence on decreasing income inequality.